Odpowiedzi

2009-12-18T15:53:18+01:00
A) (x+3y)^-9y^= x^+9y^+6xy-9y^=x^+6xy
b) (b+3)^-(b-3)^=b^+9+6b-(9-6b+b^)=b^+9+6b+9+6b-b^=12b+18
c) 2(3+b)^-12b=2(9+6b+b^)-12b=18+12b+2b^-12b=18+2b^
d) (3x-2)^+2(x+3)^=9x^+4-12x+2(x^+9+6x)=9x^+4-12x+2x^+18+12x=
=11x^+22
2009-12-18T15:53:34+01:00
A) (x+3y)^-9y^= x^ + 9y^+ 6xy - 9y^ = x^ + 6xy
b) (b+3)^-(b-3)^= b^ + 9 + 6b -(9 - 6b + b^) = b^ + 9 + 6b - 9 + 6b - b^ = 12b
c) 2(3=b)^-12b= 2 (9 + 6b + b^)-12b = 18 + 12b + 2b^- 12b = 18 + 2b^
d) (3x-2)^+2(x+3)^= 9x^ + 4 - 12x + 2(x^ + 9 + 6x) = 9x^ + 4 - 12x + 2x^ + 18 + 12x = 11x^ + 22







  • Użytkownik Zadane
2009-12-18T15:57:51+01:00
A) (x+3y)²-9y²=
x²+6xy+9y²-9y²=
x²+6xy

b) (b+3)²-(b-3)²=
b²+6b+9 - b²+6b+9=
6b+9+6b+9 =
12b+18

c) 2(3+b)²-12b=
2(9+6b+b²)-12b=
18+12b-2b²-12b=
18-2b²
(przy założeniu że po trójce jest plus)



d) (3x-2)²+2(x+3)²=
9x²-12x+4+2(x²+6x+9)=
9x²-12x+4+2x²+12x+18=
9x²+4+2x²+8=
11x²+12